(untitled) (Research, Society and Development, 2022)
Cancer triggers organic and emotional reactions, causing feelings, imbalances and internal conflicts. Given this scenario, there is a growing need for qualified professionals to develop care for oncological children. The study aimed to understand the role of nurses in humanized care for hospitalized cancer patients, bringing two categories: nursing care to hospitalized cancer patients and nurses’ contributions to humanized care for hospitalized cancer patients. This is an integrative review research, carried out through a bibliographic review: articles available in Portuguese, from 2018 to 2022, where 13 articles were used for the study. The act of caring is an action whose goal is the child’s life, involves creating a bond with the caregiver and patient. In addition, nurses must promote strategies to promote better care. It is concluded that the nurse is able to perform humanized care, seeking scientific knowledge and empathy for that child and his family.